Improved parameter estimation for MRF models for varying current - M. Razali, M. Khusyaie; Abdul Muthalif, Asan Gani; Nordin, N. H.Diyana; Abdul Hamid, Syamsul Bahrin (American Scientific Publishers, 2017)
This paper introduces the improved parameter estimation of Magnetorheological fluid (MRF) damper models for varying input current. The models being studied for the estimation are Bingham model, Simple Bouc-Wen model, Modified Bouc-Wen model, Hyperbolic Tangent Function model, and Nonlinear Biviscous model. In estimating the parameters of the models, a comparison between the simulation and the experimental results are made. The mathematical equations of each parameter are established as a function of the input current through curve fitting method. In order to optimize the estimation, the mathematical equations are divided into two range. It is found out that the model with the least value of parameter estimation error is Modified Bouc-Wen.